Origin of Langerhans cells in normal skin and chronic GVHD after hematopoietic stem‐cell transplantation. Issue 1 (30th December 2013) - Andani, Rafiq; Robertson, Ivan; MacDonald, Kelli P. A.; Durrant, Simon; Hill, Geoffrey R.; Khosrotehrani, Kiarash
Abstract: Chronic graft‐versus‐host disease (cGVHD) is a common complication following allogeneic stem‐cell transplantation (SCT). Past studies have implicated the persistence of host antigen‐presenting cells (APCs) in GVHD. Our objective was to determine the frequency of host Langerhans cells (LCs) in normal skin post‐SCT and ask if their persistence could predict cGVHD. Biopsies of normal skin from 124 sex‐mismatched T‐cell‐replete allogenic SCT recipients were taken 100 days post‐transplant. Patients with acute GVHD and those with <9 months of follow‐up were excluded and prospective follow‐up information was collected from remaining 22 patients. CD1a staining and X and Y chromosome in‐situ hybridization were performed to label LCs and to identify their host or donor origin. At 3 months, 59 ± 5% of LCs were host derived. The density of LCs and the proportion of host‐derived LCs were similar between patients that did or did not develop cGVHD. Most LCs in the skin remained of host origin 3 months after SCT regardless of cGVHD status. This finding is in line with the redundant role of LCs in acute GVHD initiation uncovered in recent experimental models.